Investigation of galleria mellonella microbiome to determine its species composition (Experimental biology, 2021)
Microbiome research is a key important method of microbiological research that can be beneficial in solving modern problems. Organisms with a normal microbiome are less susceptible to pathogens, as well as, probiotic features of symbiotic bacteria in the microbiome positively act in their sustainable development and survival. The current study aimed to characterize the gut microbiome of greater wax moth larvae – Galleria mellonella and its species composition. A total of 38 bacterial isolates from the gut microbiome of greater wax moth larvae were identified by using 16S rRNA gene analysis. Isolates of microorganism from G. mellonella larvae could be grouped into three phyla: Bacillus (60%), Rhizobium (20%), and Pseudomonas (20%). Morphological and phylogenetic analysis showed that bacterial strains belonging to Bacillus amyloliquefaciens, Bacillus velezensis, Bacillus subtilis, Rhizobium pusense and Pseudomonas parafulva and were dominant in the gut microbiome Galleria mellonella. Bacterial strains isolated from larvae gut separately can be used in biotechnology, agriculture, and ecology.
Keywords: Galleria mellonella, gut microbiome, 16S rRNA sequencing